2023
DOI: 10.1002/jcu.23336
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac remodeling from the fetus to adulthood

Abstract: Prenatal cardiac remodeling refers to in utero changes in the fetal heart that occur as a response to an adverse intrauterine environment. In this article, we will review the main mechanisms leading to cardiac remodeling and dysfunction, summarizing and describing the major pathological conditions that have been reported to be related to this in utero plastic adaptive process. We will also recap the current evidence regarding the persistence of fetal cardiac remodeling and dysfunction, both in infancy and late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 120 publications
0
3
0
Order By: Relevance
“…The fetal heart is essential for the hemodynamic response to damage such as chronic hypoxia, pressure and volume overload, toxins, and infections. An insult can directly damage or overload the myocardium 22 . Fetal Doppler indices and MPI have been used for a long time to measure cardiac function and blood flow in fetuses with fetal growth restriction, preeclampsia, and pregestational diabetes mellitus 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…The fetal heart is essential for the hemodynamic response to damage such as chronic hypoxia, pressure and volume overload, toxins, and infections. An insult can directly damage or overload the myocardium 22 . Fetal Doppler indices and MPI have been used for a long time to measure cardiac function and blood flow in fetuses with fetal growth restriction, preeclampsia, and pregestational diabetes mellitus 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…During fetal development, the cardiovascular system is exquisitely sensitive to intrauterine environmental cues. Although adaptive in the short term, changes in cardiac structure and function set in motion by the intrauterine environment may be seen postnatally and increase susceptibility to disease later in life [ 19 , 20 ]. In the current study, we found that, among the cardiac parameters measured, mean LVMI was approximately 30% higher in toddlers with versus without in utero exposure to maternal SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…As an experimental model, we used rats exposed to undernourishment conditions during fetal life, induced by maternal undernutrition during gestation (MUN rats). This animal model mimics an adverse fetal environment that leads to intrauterine growth restriction in humans, which is an important risk factor in the development of hypertension and CVD [ 30 , 31 ]. We characterized the MUN rat model and showed that male rats develop hypertension in adult life, while females show a mild form of hypertension during aging [ 19 ].…”
Section: Discussionmentioning
confidence: 99%